INDUCED PYCNlDlA PRODUCTION BY THE SOYBEAN ISOLATES OF RHIZOCTONIA BATATlCOLA - A. K. SARBHOY, VISHWA DHAR* and (Indian Phytopathology, 2002)
Pycnidia formation in four soybean isolates of R. bataticola has been artificially induced on fresh stem pieces of soybean. Comparison of some other substrate for sporulation showed that stem pieces were most preferred followed by leaf pieces. The pycnidia forming principle appeared to be thermostable. A fluctuating temperature of 28 ± 6°C and constant temperature of 20 ± 1°C supported profuse pycnidia formation. Light played an important role in sporulation and the best results were obtained under diurnal exposure of 12h light darkness during incubation. Increased length of darkness had a detrimental effect. Based on the results obtained from different experiments, a simple and reliable technique for profuse sporulation of soybean isolates of R. bataticola has been described.